Effect of nanofluids on heat transfer characteristics of a heat pipe / Amin Kamyar - Amin, Kamyar (2013)
Thermosyphons are widely used in thermal engineering application such as cooling of electronics and waste heat recovery thanks to their passive cooling ability. Performance of thermosyphons could be improved by various means like changing the transport properties and heat transfer characteristics of the working fluid. Nanofluid, referring to a colloidal suspension of a base fluid and nanosized (1-100 nm) solid particles, is an option to achieve this target. Combining the heat exchange nature of thermosyphons and distinct thermal characteristics of nanofluids can open up new horizons in the field of heat transfer. Current study concentrates on the thermal performance of a two-phase closed thermosyphon filled with two nanofluids using water as the base fluid mixed with Al2O3 and TiSiO4 nanoparticles. Nanofluids were prepared in different volumetric concentrations (0.01%, 0.02%, 0.05% and 0.075) and different heat loads (40W, 70W, 120W, 180W and 210W) were provided in the evaporator section. Results demonstrate that both nanofluids improve the performance through reduction in thermal resistance by 65% (at 0.05 vol.% for Al2O3) and 57% ( at 0.075 vol.%). Other improvements were also found in the form of increase in heat transfer coefficient and decrease in evaporator wall temperature. For all the working fluids, heat transfer coefficient increases with increase in input power. Both nanofluids cause the heat transfer coefficient rise compared to that of pure water. The maximum value for heat transfer coefficient occurred at 0.05 vol.% for alumina nanoparticles, while this value took place at 0.075 vol.% for TiSiO4/water nanofluid. Temperature distribution along the thermosyphon, decreased after using nanofluids as the working fluid.